Fitoquímica e bioatividade de Miconia burchellii Triana (Melastomataceae) - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
Although the Miconia genus is the largest representative of the Melastomataceae family, the number of studies involving phytochemistry and the evaluation of the biological activities of the species that compose it is still very small. In this context, this work aimed to carry out the phytochemical study and evaluate the antibacterial and cytotoxic activities of Miconia burchellii Triana, a species that has not yet been studied in terms of its chemical constituents and biological activities. Phytochemical study of the leaves and stem bark led to the identification of twenty substances, including triterpenes, saponins, flavonoids, pheophorbides and a steroid. Among these compounds, six are being reported in the literature for the first time: the triterpenes 3-O-β-trans-p-coumaroyl-1α-hydroxy-urs-12-en-28-oic acid and 3-O-β- cis-p-coumaroil-1α-hydroxy-urs-12-en-28-oic acid, obtained as a mixture through the ethyl acetate fraction of M. burchellii leaves; and the saponins 1α,3β,23-trihydroxy-olean-12-en-28-oic acid 28-O-β-glycopyranoside ester, 1α,3β,23-trihydroxy-urs-12-en-28-oic acid 28-O-β-glycopyranoside ester, 3-O-β-galloyl-1α,23-dihydroxy-olean-12-en-28-oic acid 28-O-β-glycopyranoside ester and 3-O-β-galloyl-1α,23-dihydroxy-urs-12-en-28-oic acid 28-O-β-glycopyranoside ester, obtained as isomeric mixtures from the methanol fraction of leaves. These substances had their structures elucidated through nuclear magnetic resonance in one and two dimensions, in addition to high resolution mass spectrometry. The crude extract and the ethyl acetate and methanol fractions of the stem bark were the most active against the tested bacteria, showing growth inhibition of both Gram-positive (Staphylococcus aureus and Staphylococcus epidermidis) and Gram-negative (Escherichia coli and Pseudomonas aeruginosa), with MIC (minimum inhibitory concentration) values ranging from 62.5 to 1000 μg/mL. Regarding cytotoxicity, the hexane and ethyl acetate fractions from the stem bark showed greater selectivity in inhibiting colon tumor cells (HCT-116) and leukemia (HL-60) compared to nontumor cells (L-929). Among the substances tested, ethyl pheophorbid A was cytotoxic against the leukemia strain, with an IC50 (half maximal inhibitory concentration) of 4.74 μg/mL.
Phytochemistry and bioactivity of Miconia burchellii Triana (Melastomataceae)
Keywords: Atividade antibacteriana; Citotoxicidade; Feoforbídeo; Flavonoide; Saponina; Triterpeno; Antibacterial activity; Cytotoxicity; Pheophorbid; Flavonoid.; Saponin; Triterpene; Fitoquímica; CIENCIAS EXATAS E DA TERRA::QUIMICA